2017
DOI: 10.2967/jnumed.117.194555
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, Biodistribution, and Radiation Dosimetry for 89Zr-Trastuzumab in Patients with Esophagogastric Cancer

Abstract: Trastuzumab with chemotherapy improves clinical outcomes in patients with human epidermal growth factor receptor 2 (HER2)-positive esophagogastric adenocarcinoma (EGA). Despite the therapeutic benefit, responses are rarely complete, and most patients develop progression. To our knowledge, this is the first report evaluating Zr-trastuzumab in HER2-positive EGA; here, we evaluate the safety, pharmacokinetics, biodistribution, and dosimetryZr-trastuzumab. Trastuzumab was conjugated with deferoxamine and radiolabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
97
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(104 citation statements)
references
References 28 publications
3
97
0
4
Order By: Relevance
“…We previously reported that 89 Zr-trastuzumab localizes to HER2-positive EG tumors as measured by PET imaging (26). Furthermore, in contrast to 18 F-FDG and 18 F-FLT PET, 89 Zrtrastuzumab PET could noninvasively differentiate HER2positive from HER2-negative EG cancers preclinically (15).…”
Section: Homogenous 89 Zr-trastuzumab Uptake On Pretreatment Pet Maymentioning
confidence: 99%
“…We previously reported that 89 Zr-trastuzumab localizes to HER2-positive EG tumors as measured by PET imaging (26). Furthermore, in contrast to 18 F-FDG and 18 F-FLT PET, 89 Zrtrastuzumab PET could noninvasively differentiate HER2positive from HER2-negative EG cancers preclinically (15).…”
Section: Homogenous 89 Zr-trastuzumab Uptake On Pretreatment Pet Maymentioning
confidence: 99%
“…HER2-targeted PET imaging using 89 Zr-trastuzumab has been investigated as an immuno-imaging method for gastric cancer. A clinical study showed a high degree of accumulation of 89 Zr-trastuzumab in the foci of esophagogastric cancer patients [25], and a preclinical study using gastric cancer xenograft mice showed the highest tumor uptake of 34.4% ID/g at 96 h p.i. [26].…”
Section: Discussionmentioning
confidence: 99%
“…Readers interested in these efforts are directed to a comprehensive review by Heskamp et al 131 Though little clinical data is available on the metabolism of 89 Zr-labeled antibodies, it is interesting to note that the bone uptake patterns observed in mice are typically not seen in humans, leading many to believe that DFO is indeed a suitable chelator for 89 Zr in the clinic. 97,[132][133][134][135][136] Studies using 89 Zr-DFO-labeled trastuzumab in HER2-positive esophagogastric adenocarcinoma 136 and 89 Zr-labeled cmAb-U36 antibody in head and neck cancer 131 reported relatively low activity accumulation and retention in the liver and spleen. In contrast, higher activity concentrations were observed in both organs during trials with 89 Zr-huJ591, 97 89 Zrcetuximab, 133 and 89 Zr-rituximab.…”
Section: Zirconium-89mentioning
confidence: 99%